Role of Rail in Passenger Border Traffic between Poland and Ukraine — a Dynamic Approach - Komornicki, Tomasz; Kowalczyk, Karol (Regional Barometer. Analyses & Prognoses, 2018)
Changes in the functions of Polish borders at the turn of the 20th and 21st century resulted in a reorientation of transport connections with countries of the former Soviet Union. One of the consequences of the phenomenon are considerable transformations in the scope of degree of use of rail transport in cross-border passenger traffic. The objective of the article is the dynamic assessment of the importance of railways in passenger traffic between Poland and Ukraine in the years 1990–2016 (including limited data for 2018), with consideration of the infrastructural and organizational factors. The analyses employed data on traffic of persons and vehicles on railway and road border crossings. They provided the basis for the determination of changes in the position of rail towards other modes of cross-border transport. The second source is Network Train Timetable (in Polish: Sieciowy Rozkład Jazdy Pociągów), used for the preparation of maps of connections functioning in selected time intervals. The analyzed period was characterized by a continuous decrease in the importance of rail in bilateral passenger traffic. It proved completely inflexible towards systemic and geopolitical transformations and intermodal competition of bus transport, and from 2013 also air transport. The spatial layout of rail connections suggested initial de-concentration involving several border crossings, and then concentration on two main lines. The vast general increase in traffic that occurred in recent years in the Ukrainian direction constitutes a chance for increasing the role of rail transport in a situation of overload of road border crossings.